2014
DOI: 10.1177/1352458513517591
|View full text |Cite
|
Sign up to set email alerts
|

Colour vision impairment is associated with disease severity in multiple sclerosis

Abstract: Colour vision impairment is associated with greater MS severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 29 publications
0
29
0
1
Order By: Relevance
“…In this model including GCC thickness, thalamus volume, and lesions within the ORs, only GCC thickness remained statistically significant [OR = 0.89 95 % CI (0.81-0.98) p = 0.023]. When we added disease duration, age, and sex also as covariates to the previous model, the results were HRR scores have been linked to disease severity and neuroaxonal damage [6]. Moreover, Saidha S and colleagues have recently described that retinal atrophy parallels brain atrophy [20].…”
Section: Risk Of Dyschromatopsia By Retinal and Brain Damagementioning
confidence: 52%
See 2 more Smart Citations
“…In this model including GCC thickness, thalamus volume, and lesions within the ORs, only GCC thickness remained statistically significant [OR = 0.89 95 % CI (0.81-0.98) p = 0.023]. When we added disease duration, age, and sex also as covariates to the previous model, the results were HRR scores have been linked to disease severity and neuroaxonal damage [6]. Moreover, Saidha S and colleagues have recently described that retinal atrophy parallels brain atrophy [20].…”
Section: Risk Of Dyschromatopsia By Retinal and Brain Damagementioning
confidence: 52%
“…Given that dyschromatopsia has been linked to disease severity and markers of diffuse neuroaxonal damage [6], we assessed the role of GCC thickness in dyschromatopsia development in MS independently of NBPV and T1 MPRAGE lesion load. We found that preserving one micron in GCC thickness was associated with a 12 % lower probability of color vision impairment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 In addition to impaired HCVA and LCVA, patients with MS are commonly found to have impaired color vision, both with and without a history of ON. [44][45][46] Recent studies using OCT have observed that performance in tests of color vision is strongly correlated with thickness of RNFL 43,47 and PMB, 43,47 as well as TMV, 47 in MS patients. These associations are stronger when using SD-OCT technology than with TD-OCT, reflecting the superior resolution and accuracy of the former.…”
Section: Relationship Of Oct Parameters With Clinical Outcome Measuresmentioning
confidence: 99%
“…LCVA testing using 2.5% contrast charts has emerged from this work as a test that is sensitive for detecting visual disability and tracking it over time (9, 10). RNFL thickness is another informative outcome measure increasingly utilized in clinical practice and trials (6, 11) and color vision is frequently impaired in MS patients with and without a history of optic neuritis (12, 13). Because most of these tests have not been evaluated in patients with moderate to severe visual dysfunction, whether these instruments will be useful across the full spectrum of MS patients has yet to be established.…”
Section: Introduction1mentioning
confidence: 99%